Additional Sanction as an Effort to Restore the Environment Due to Land Fires - Mubarak, Ridho; Syahrin, Alvi; ., Marlina; Danil, Elwi (KnE Social Sciences, 2024)
Environmental damage in Indonesia has directly impacted human life, one of which is forest/land fires. Burning forests and land can be considered a form of crime because the action has an impact that can harm the interests of many people. Perpetrators of forest and land fire crimes can be subject to two types of sanctions, namely the main criminal sanctions and additional sanctions. This study aimed to discuss how to apply additional punishment in environmental crimes due to land fires. The study’s approach used to conduct this study is of normative law studies. This method focuses on analyzing positive and general legal principles. The application of additional criminal sanctions in Law Number 32 of 2009 is an additional penalty to cover the deficiencies of the principal criminal. Where the maximum fine sanction has a special maximum provision that is less than how much money lost or incurred because of additional criminal acts. The Act for Environmental Management and Protection verbally expressively accommodates the concept of a double-track system, namely the imposition of criminals and additional criminal sanctions simultaneously on perpetrators of environmental crimes. If additional criminal sanctions, in the form of recovery, cannot be carried out by corporations, then additional criminal sanctions that are equivalent and repressive in the form of confiscating assets or closing all or part of business activities can be used as suspension of sanctions. Keywords: additional penal, environment recovery, fire